Transformasi: Inovasi Produk Pemanfaatan Limbah Kopi Menjadi Briket Arang di Kecamatan Kertasari Desa Sukapura: Pengabdian - Wulan Ramadhani; Oqa Vraja Vatoe Rachman; Mutiara Imansari; Fathimah Aulia Rahma; Hilmi Nabil Muzakky; Gina Aulia Amalia; Idzni Fatasya Zulqisthi; Filah Pebrianti; Hikmal Abror; Muhamad Deva Fathurahman; Miftahudin Faqih (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Community Service Program (KKN) of Muhammadiyah University of Bandung in Sukapura Village, Kertasari District, Bandung Regency, is implemented as a form of community service to address key issues such as low public awareness of coffee waste processing. The goal of this empowerment program is to provide knowledge and encourage residents of each neighborhood unit (RT/RW) in Sukamaju Hamlet to utilize coffee waste to produce charcoal briquettes, which have both economic and environmental value. The empowerment activities consist of observations and interviews with coffee factory owners, followed by a briquette-making simulation, and community outreach seminars. The briquettes produced use a natural binder, tapioca starch. This empowerment program not only contributes to coffee waste reduction but also opens up new business opportunities for the community. Thus, the role of KKN students in empowering the community has proven effective in increasing knowledge and raising awareness regarding the benefits of coffee waste.